PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI LAHAN NON-FUNGIBLE TOKEN (NFT) BERDASARKAN UNDANG-UNDANG NO. 4 TAHUN 2023 - Sinambela, Krisman Josua; Janpatar Simamora; Ria Juliana Siregar (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
The development of digital technology has enabled the emergence of Non-Fungible Tokens (NFTs) as digitally authenticated assets recorded on blockchain networks, including their use in representing ownership of digital land within metaverse ecosystems. However, Indonesia has not yet formulated explicit regulatory provisions governing the legal classification of NFTs, the scope of supervisory authority, or the standards for consumer protection. This regulatory absence results in legal ambiguity regarding the placement of NFTs within the framework of Financial Sector Technology Innovation (ITSK) under Law No. 4 of 2023, and simultaneously presents risks to consumers, including fraud, data misuse, loss of access to digital assets, and a lack of clear accountability mechanisms on NFT platforms. This research examines the legal status of NFTs in relation to ITSK and analyzes the adequacy of current consumer protection measures in NFT-based digital land transactions. Through a normative juridical method, the study finds that NFTs have not been formally classified within ITSK, nor assigned to a definitive supervisory authority, whether OJK or Bappebti. As such, consumer protection remains reliant on general norms under Law No. 8 of 1999, which are insufficient to address the specific risks inherent in NFT transactions. This research recommends the issuance of derivative regulations by OJK and/or Bappebti to clarify NFT classification, establish platform obligations, and strengthen consumer protection.